Appropriate vacuolar acidification in Saccharomyces cerevisiae is associated with efficient high sugar fermentation. (April 2018) - Nguyen, Trung D.; Walker, Michelle E.; Gardner, Jennifer M.; Jiranek, Vladimir
Abstract: Vacuolar acidification serves as a homeostatic mechanism to regulate intracellular pH, ion and chemical balance, as well as trafficking and recycling of proteins and nutrients, critical for normal cellular function. This study reports on the importance of vacuole acidification during wine-like fermentation. Ninety-three mutants (homozygous deletions in lab yeast strain, BY4743), which result in protracted fermentation when grown in a chemically defined grape juice with 200 g L −1 sugar (pH 3.5), were examined to determine whether fermentation protraction was in part due to a dysfunction in vacuolar acidification (VA) during the early stages of fermentation, and whether VA was responsive to the initial sugar concentration in the medium. Cells after 24 h growth were dual-labelled with propidium iodide and vacuolar specific probe 6-carboxyfluorescein diacetate (6-CFDA) and examined with a FACS analyser for viability and impaired VA, respectively. Twenty mutants showed a greater than two-fold increase in fluorescence intensity; the experimental indicator for vacuolar dysfunction; 10 of which have not been previously annotated to this process. With the exception of Δhog1, Δpbs2 and Δvph1 mutants, where dysfunction was directly related to osmolality; the remainder exhibited increased CF-fluorescence, independent of sugar concentration at 20 g L −1 or 200 g L −1 . These findings offer insight to the importance of VA to cell growth in high sugar media. Highlights: Vacuolar acidification (VA) is related to successful fermentation in a high sugar medium. pH sensitive 6-carboxyfluorescein diacetate used to measure vacuolar dysfunction. Impaired acidification measured as increased fluorescence in 20 deletion mutants. 10 genes (previously not annotated to VA, shown to be affected using 6-CFDA).